LEADERSHIP BASED ON INSTITUTIONAL ORIENTATION IN IMPROVING THE QUALITY OF HEALTH EDUCATION(STUDY AT STIKES BUDI LUHUR INDONESIA AND MAHSA UNIVERSITY MALAYSIA) - Waska Warta; Puteri Noralina Binti Megat Ramli, Muzahir Bin Mohamad; Damai Yanti, Yosi Oktri; Selvia Ruyatus Saefullah (International Journal of Teaching and Learning, 2024)
The objective of this study is to examine the leadership styles employed at STIKES Budi Luhur Indonesia and Mahsa University Malaysia in their endeavors to enhance the quality of health education, with a particular focus on leadership rooted in institutional orientation. Both universities have demonstrated a firm dedication to improving the quality of education through the use of distinct yet equally successful leadership approaches. STIKES Budi Luhur prioritizes the creation of a curriculum that aligns with the requirements of the healthcare sector, while also focusing on enhancing soft skills and fostering religious character. In contrast, Mahsa University Malaysia prioritizes enhancing the caliber of its professors by providing regular training, modernizing facilities and infrastructure, and integrating information and communication technologies into the learning process. The study reveals that despite variations in leadership strategies, both schools effectively establish a favorable, inventive, and competitive learning atmosphere. The results of this study are anticipated to offer significant perspectives for leaders of similar higher education health institutions in developing successful leadership strategies to improve educational excellence.